2014
DOI: 10.3944/aott.2014.13.0119
|View full text |Cite
|
Sign up to set email alerts
|

Cementless bipolar hemiarthroplasty for unstable intertrochanteric fractures in octogenarians

Abstract: Cementless bipolar hemiarthroplasty appears to be a suitable method for the treatment of intertrochanteric fracture in octogenarians. However, stable fixation of the posteromedial fragment is necessary to avoid stem subsidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…5,29) Our current study also supported the results reported in the literature (19% in cementless group and 27% in cemented group).…”
Section: Grade Bsupporting
confidence: 92%
“…5,29) Our current study also supported the results reported in the literature (19% in cementless group and 27% in cemented group).…”
Section: Grade Bsupporting
confidence: 92%
“…There were 19 studies that used cemented stem, 14 that used cementless stem, and two comparative studies that used both stems. Eleven studies were prospective studies, which used methods with wires, cables, and sutures for fixation of fracture fragments 1 2 4 11 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42) .…”
Section: Resultsmentioning
confidence: 99%
“…In the hemiarthroplasty technique the prosthesis metaphyseal fit should be obtained by reconstructing the comminuted calcar and the greater trochanter or by the bone cement mantle if the distorted comminuted fragments cannot be restored. Kim y et al reported that comminuted posteromedial fragments should be stably fixed to avoid stem subsidence [23] . This complex surgical technique prolongs the surgery time and increases the blood loss and infection rate.…”
Section: Discussionmentioning
confidence: 99%